A Novel Solar Photovoltaic Fed TransZSI-DVR for Power Quality Improvement of Grid-Connected PV Systems - Moghassemi A.; Padmanaban S.; Ramachandaramurthy V.K.; Mitolo M.; Benbouzid M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric fault currents; Electric power transmission networks; Voltage regulators; Dynamic voltage restorer (DVR); Grid connected PV system; Lower voltage stress; Maximum constant boost controls; Photovoltaic systems; Point of common coupling; Power quality improvement; Voltage disturbances; Power quality